OP0249 Multi-biomarker disease activity and autoantibody status lead to cost effective tapering algorithms in rheumatoid arthritis patients in sustained remission. (15th June 2017) - Hagen, M; Englbrecht, M; Haschka, J; Reiser, M; Kleyer, A; Hueber, A; Manger, B; Figuereido, C; Cobra, J Fogagnolo; Tony, H-P; Finzel, S; Kleinert, S; et al.
Abstract : Background: Achieving remission is the ultimate treatment goal in patients with rheumatoid arthritis (RA). With the development and wider use of highly effective disease modifying anti-rheumatic drugs (DMARD) about half of RA patients reach the disease remission state (1), raising the question about tapering or stopping anti-rheumatic treatment and appropriate predictors (2). Objectives: To analyse the effect of a risk-stratified DMARD tapering algorithm based on multiple-biomarker disease activity (MBDA) score and anti-citrullinated protein (ACPA) status for successful DMARD tapering and treatment cost reduction in RA patients in sustained remission enrolled in the prospective randomized controlled RETRO study (3, 4). Methods: MBDA scores and ACPA status were determined in the baseline samples of 146 patients in sustained remission. Patients either continued DMARDs (arm1), tapered dose by 50% (arm 2) or stopped DMARDs after tapering (arm 3) for one year according to the RETRO study protocol. Direct treatment costs (including testing costs at baseline) were evaluated every three months. MBDA and ACPA status were used as predictors creating a risk-stratified tapering algorithm based on relapse rates. Results: RA patients with a low MBDA score (<30) and negative ACPA showed lowest relapse risk (19%). With either single positivity for ACPA or moderate/high MBDA scores (≥30) relapse risk increased and was high in double-positive patients (61%). In MBDA negative (<30) and MBDA single-positive (≥30) groups, DMARD tapering appears feasible. Considering only patients that did not flare, costs for synthetic and biologic DMARDs in the MBDA-negative and single-positive groups (n=41) would have been 123.751, 29€ for full-dose treatment over one year. Tapering and stopping DMARDs in this low-risk relapse groups allowed a reduction of 92.821, 50€ (-75%) of DMARD costs. Average reduction of DMARD costs per patient were 2.350, 08€ in the double negative (MBDA- /ACPA-) and single negative (MBDA- /ACPA+) group and 1.761, 43€ in the MBDA single positive (MBDA+ /ACPA-) group. Conclusions: Combining MBDA score and ACPA status allows risk stratification for successful DMARD tapering and cost-effective use of biologic DMARD. Given that previous data of the RETRO have shown that patients relapsing after tapering their DMARDs respond well to their reintroduction, a stratified tapering and stopping of DMARDs is not only a cost economic but also clinically feasible strategy. References: Aga AB et al. Ann Rheum Dis. 2013;74:381–8. Schett G et al. Ann Rheum Dis. 2016 Aug;75(8):1428–373. Haschka J et al, Ann Rheum Dis. 2016;75:45–51. Rech J et al, Ann Rheum Dis. 2015; Oct. 19. Disclosure of Interest: None declared